A cross sectional study to assess the expressed COVID-19 preventive practices among the health care workers and public visiting tertiary care hospital, AIIMS, Jodhpur - Mukesh C Sharma; V A Raghu; Manish K Balai (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The corona virus disease-2019 (COVID-19) infection is a current public health crisis, and it is challenging to the world health-care system. As there is no treatment, prevention is the crucial importance to break the chain of transmission of infection and prevent fatality among the high-risk populations. The aim of the study was to assess the Expressed COVID-19 preventive practices among health-care workers (HCWs) and the public visiting tertiary care hospital, AIIMS, Jodhpur. METHODOLOGY: A cross-sectional study was conducted among 406 HCWs and 238 public, recruited by convenient sampling technique. A validated and pretested self-structured practice questionnaire used to collect the data regarding COVID-19 preventive practice. The data were collected through online Google Forms and interview techniques and analyzed by software SPSS 26 version. RESULTS: Majority of 87.7% HCWs and 76.5% public always followed practice of hand wash with soap and water and sanitize for 20 s. Majority of 79.6% HCWs and 49.2% public maintain social distance in public place. Gender (χ2 = 18.806 P ≤ 0.001) and education (χ2 = 43.270 P ≤ 0.001) among HCWs and in public demographic variable income (χ2 = 21.102 P = 0.002), religion (χ2 = 13.302 P = 0.006) and source of information (χ2 = 17.030 P = 0.026) was significantly associated with level of COVID-19 preventive practice. CONCLUSION: The study showed moderate level of COVID-19 preventive practice among HCWs and public. Based on this result, an effective IEC intervention programs can be designed to educate public and HCWs and follow a safe COVID-19 preventive practice.